The Waqf Integrated Financial Instrument of Pension Model in Malaysian Social Security: A Conceptual Proposition - Ubaidillah, M.; Ismail, M. A.; Mohd Noor, M. A. (Universiti Sains Islam Malaysia, 2024)
The ageing population trend is a problem for almost all countries in the world. In Malaysia, the issue is exacerbated by insufficient employee savings to face retirement. The majority of Malaysian employees have savings no more other than mandatory savings of the Employees Provident Fund (EPF) account. On the other hand, waqf has many roles in the country’s economic development as it helps to improve welfare of the community. This paper aims to connect the gap between pension and waqf issues through a new proposed Waqf Based Pension Model. This study uses descriptive analysis to propose a Waqf Based Pension Model. This study employs library research approach to collect secondary data from journal articles, books, reports, and websites that contain existing pension schemes and waqf. This new model improves weaknesses in the existing pension scheme using annuity-based calculations. This study finds that productive waqf assets may be used to generate greater profits. In addition, waqf funds are then allocated to build the infrastructure needed by the community such as health services, education, housing, transportation and religious facilities. The new Waqf Based Pension Model is expected to be supported and applied by the government and the community.